2021
DOI: 10.1017/s0022215121001651
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammatory markers and psychophysical olfactory scores in coronavirus disease 2019 patients: is there any correlation?

Abstract: Objective To analyse the correlations between olfactory psychophysical scores and the serum levels of D-dimer, C-reactive protein, ferritin, lactate dehydrogenase, procalcitonin and neutrophil-to-lymphocyte ratio in coronavirus disease 2019 patients. Methods Patients underwent psychophysical olfactory assessment with the Connecticut Chemosensory Clinical Research Center test, and determination of blood serum levels of the inflammatory markers D-dimer, C-reactive protein, ferritin, lactat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 41 publications
2
21
1
Order By: Relevance
“…However, no clinical, epidemiological or laboratory risk factors have yet been identified [32,33]. In this study including 288 patients with COVID-19 OD, it is confirmed that no clinical or epidemiological factor predicts the evolution of OD at 2 months.…”
Section: Discussionsupporting
confidence: 62%
“…However, no clinical, epidemiological or laboratory risk factors have yet been identified [32,33]. In this study including 288 patients with COVID-19 OD, it is confirmed that no clinical or epidemiological factor predicts the evolution of OD at 2 months.…”
Section: Discussionsupporting
confidence: 62%
“…It has not yet been clarified what the frequency of persistent disturbances is in these groups of individuals, but if the prevalence recorded in cases of primary infection were confirmed, it would mean that this problem may not end with the immunization of the population. Second, the identification of the pathogenesis [54][55][56][57][58][59][60][61] and risk factors [2][3][4][5][6][7][8][9][10][11][12][62][63][64][65][66][67][68] for the development of persistent CD are in its infancy. For this reason, no effective therapies have yet been found for the prevention and treatment of COVID-19 related POD and PGD [69][70][71][72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous reports describing rates of smell recovery, very little information exists regarding the factors associated with recovery vs. non-recovery. Few have investigated this phenomenon, and to date almost no clinical, epidemiological, or laboratory markers have been identified [22] , [23] , [24] , [25] . In their study of prospectively recruited patients from 3 European centers, Saussez and colleagues examined patterns of recovery among 288 patients within 60 days of onset of olfactory dysfunction [23] .…”
Section: Discussionmentioning
confidence: 99%